THE EFFECT OF BROMOCRIPTINE ON THE LEVELS OF ALKALINE PHOSPHATASE AND LIVER OF IMMATURE MALE RATS - Jaber, Adhwaa Hameed (PT. Antis International Publisher, 2025)
Objectives: The purpose of this investigation was to ascertain how bromocriptine (BRO) affected the livers of young male rats. Method: On the first day of experiments, the first group of five immature male rats (16 days old) weighing 25–30g was slaughtered. The remaining rats were divided into four groups, each consisting of 10 animals. The 3rd and 4th groups received BRO (IP) at 3 and 6 mg/kg BW, respectively, for two periods (9 days and 27 days), whereas the second group acted as the control and received the vehicle (IP). For the recovery trial, five rats from each group were kept for a month without receiving any therapy. Results: When compared to the control group, BRO therapy resulted in: A) a substantial loss in body the weight, B) significant rise in liver weight, and C) a significant increase in blood levels of phosphatase-alkaline in immature albino rats of both treated the groups. Novelty: The current investigation leads us to the conclusion that, even though BRO had an impact on the liver of young male rats, the effects of BRO may be recovered after a month of no treatment.